Can transformative leadership, work discipline, and work motivation improve employee performance? - Syarifuddin, Syarifuddin (Advances: Jurnal Ekonomi & Bisnis, 2023)
Purpose: This study analyzes the influence of transformational leadership, work discipline, and work motivation on employee performance at the Mariso Sub-District Office in Makassar City. Understanding these relationships is essential for improving organizational effectiveness and optimizing employee performance in public institutions. Research Design and Methodology: This research adopts a quantitative approach to explaining the relationship between leadership, work discipline, motivation, and employee performance. The study employs multiple regression analysis to assess the significance and strength of these variables in influencing employee performance. Data were collected through structured questionnaires distributed to employees at the Mariso Sub-District Office and analyzed using IBM SPSS 24. Findings and Discussion: The results indicate that transformational leadership, work discipline, and work motivation all positively and significantly impact employee performance. The findings reveal that employees who experience effective leadership, adhere to high levels of discipline, and maintain strong motivation tend to perform better. Furthermore, work motivation is a key factor in enhancing productivity, where higher motivation levels lead to improved performance outcomes. Implications: This study contributes to theoretical and practical discussions on human resource management by confirming that leadership style, discipline, and motivation are crucial determinants of employee performance. The findings suggest that organizations should develop transformational leadership, reinforce work discipline, and implement effective motivation strategies to optimize employee engagement and productivity.